Criteria and indicators for sustainable forestry under Mediterranean conditions applicable in Spain at the forest management unit scale - Pablo Valls-Donderis; María C. Vallés; Francisco Galiana (Forest Systems, 2015)
Aim of study: to identify criteria and indicators (C&I) of sustainable forest management (SFM) under Mediterranean conditions. The indicators are meant to monitor changes in the provision of ecosystem services at a local scale (forest management unit, FMU). We support that if a forest provides a bundle of ecosystem services its management can be considered sustainable; thus, we adjust C&I to an ecosystem services classification.